1997
DOI: 10.1111/j.1469-8986.1997.tb02131.x
|View full text |Cite
|
Sign up to set email alerts
|

The psychopathic individual: A lack of responsiveness to distress cues?

Abstract: In this study, we investigated the psychophysiological responsiveness of psychopathic individuals to distress cues and to threatening and neutral stimuli. Eighteen psychopathic individuals and 18 incarcerated control individuals, identified using the Revised Psychopathy Checklist (Hare, 1991, The Hare Psychopathy Checklist-Revised, Toronto: Multi-Health Systems), were shown slides of these three types of stimuli, and their electrodermal responses were recorded. The psychopathic individuals showed (relative to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
1
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 459 publications
(73 citation statements)
references
References 50 publications
7
63
1
2
Order By: Relevance
“…Research has shown psychopathic individuals to present with notable emotional empathic deficiencies, like a reduced physiological responsiveness to others' distress (Blair, Jones, Clark, & Smith, 1997). Results of studies on cognitive empathy and psychopathy have been a lot more equivocal.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown psychopathic individuals to present with notable emotional empathic deficiencies, like a reduced physiological responsiveness to others' distress (Blair, Jones, Clark, & Smith, 1997). Results of studies on cognitive empathy and psychopathy have been a lot more equivocal.…”
Section: Introductionmentioning
confidence: 99%
“…Psychopaths seem to have low skin conductivity when faced with distressing stimuli, which is possibly indicative of reduced or more controlled physiological reactions (Blair, Jones, Clark & Smith, 1997). In a study on domestic violence, Gottman et al (1995) registered the psychophysical responses of the batterers during heated arguments with their partners; the expectation being that the batterers would show higher responses.…”
Section: The Psychopathic Batterer: a Non-psychopathological Profile mentioning
confidence: 99%
“…They found that psychopathic individuals compared to controls displayed hyporesponsivity to the distress cues, but intact responsivity to the threat cues and neutral stimuli (R. J. R Blair et al, 1997). Further research suggests that this emotional impairment may be specific to fearful or negative emotions.…”
Section: Emotion Deficits In Psychopathymentioning
confidence: 97%
“…For example, Blair and colleagues examined skin conductance responses to visual distress cues, threat cues, and neutral stimuli in a sample of male, psychopathic criminals and nonpsychopathic criminals and found that psychopathic individuals compared to controls displayed hyporesponsivity to the distress cues but intact responsivity to the threat cues and neutral stimuli (R. J. R Blair, Jones, Clark, & Smith, 1997). Further support for the emotional impairment of psychopathic individuals is provided by research that demonstrates that psychopathic individuals are selectively impaired in recognizing the fearful facial expressions of others (R. J.…”
Section: Psychopathy and Affective Deficitsmentioning
confidence: 99%
See 1 more Smart Citation